Analysis of the implementation of the 11th ASEAN Para Games in Indonesia - Margareta Suryani; Sapta Kunta Purnama; Fadilah Umar; Slamet Riyadi (Universidad de Murcia, 2024)
Article accepted. The article will be published here soon. Pending final quality checks.